The placement of public art. Two examples on Lisbon’s waterfront - Ochoa, R. (World Multidisciplinary Civil Engineering-Architecture-Urban Planning Symposium 2017, WMCAUS 2017, 2017)
In our contemporary cities, some public spaces seem to have greater ability to host art interventions, like historical centers, urban sprawl areas, gardens and parks, new residential districts, among others. Also in port cities, its waterfronts constitute privileged spaces for the placement of public art. On Lisbon's riverfront, we can see a relevant number of works and of monuments of strong symbolic nature. In turn, the placement of public art is a way to value the inherently symbolic nature of the waterfronts and to emphasize its monumentality. However, the criteria for the placement of public art on those spaces are not always clear. In some cases, there are some thematic correspondences between the works and the places, namely with the theme of the water, the Discoveries and others like that. Nevertheless, we cannot observe a profound spatial integration, or a design with the context. In some cases, the artistic elements are produced with a logic of isolated work of art and later they are acquired and placed in some public space. In other cases, we assist to an unusual situation: A work is conceived in a strict relation with a place, but then, without any evident justification, it is dislocated to a completely different context. Or simply it is removed, disappearing from the public space. Although it seems a strange situation, such kind of dislocations often occurs in Lisbon. On this framework, this research proposes a discussion about the processes of implementation of public art. We will analyze two cases of public art replacement:1) The monument Primeira Travessia Aérea do Atlântico Sul (First Aerial Crossing of the South Atlantic), by Laranjeira Santos and Rodrigues Fernandes, 1972; and 2) The public sculpture Ribeira das Naus, by Charters de Almeida, 1995. Both works were designed to very specific and important places on Lisbon's waterfront and both were later replaced to other locations on the inner city, quite far from the river. This kind of "(de)monumentalization" of a space originates the following questions: why is a work removed from a public space and why it is decided to give it another destination? What are the implications of those changes? Is public art removable? Considering public art besides its purely aesthetic significance, this phenomenon seems to reveal that the physical and the social integration with the place are not always important, or, at least, they are only important in some moments. Also, we can see it from another point of view: A removal or a replacement of a work always reveals specific strategies for certain places, in certain moments. We can thus conclude that the processes of implementation of public art are clearly indicators of the policies and of the dynamics of the cities.